ANALISIS SEMIOTIKA ROLAND BARTHES - Sudariyah Sudariyah (Lembaga Pengembangan Kinerja Dosen, 2022)
Da'wah through film is considered effective because film has advantages that other media do not have. Film media has advantages as a propaganda medium. Da'i in conveying his da'wah message can be played by a player character in a film production, it doesn't have to be a lecture like taklim. Indirectly, the audience does not feel that they are being lectured on. Da'wah messages in films are easier to convey to the public. The research used is qualitative research. This study describes how Roland Barthes's Semiotics analysis is contained in the film